Vaccination practices of pediatric oncologists from eight states - Karely M. van Thiel Berghuijs; Heydon K. Kaddas; Echo L. Warner; Douglas B. Fair; Mark Fluchel; Elizabeth D. Knackstedt; Anupam Verma; Deanna Kepka; Adam L. Green; Andrew B. Smitherman; Lauren Draper; Rebecca H. Johnson; et al. (BMC Health Services Research, 2023)
Abstract Background Vaccinations are a vital part of routine childhood and adolescent preventive care. We sought to identify current oncology provider practices, barriers, and attitudes towards vaccinating childhood and adolescent cancer patients and survivors. Methods We conducted a one-time online survey distributed from March-October 2018 to pediatric oncologists at nine institutions across the United States (N = 111, 68.8% participation rate). The survey included 32 items about vaccination practices, barriers to post-treatment vaccination, availability of vaccinations in oncology clinic, familiarity with vaccine guidelines, and attitudes toward vaccination responsibilities. Descriptive statistics were calculated in STATA 14.2. Results Participants were 54.0% female and 82.9% white, with 12.6% specializing in Bone Marrow Transplants. Influenza was the most commonly resumed vaccine after treatment (7030%). About 50%-60% were familiar with vaccine guidelines for immunocompromised patients. More than half (62.7%) recommended that patients restart most immunizations 6 months to 1 year after chemotherapy. Common barriers to providers recommending vaccinations included not having previous vaccine records for patients (56.8%) or lacking time to ascertain which vaccines are needed (32.4%). Of participants, 66.7% stated that vaccination should be managed by primary care providers, but with guidance from oncologists. Conclusions Many pediatric oncologists report being unfamiliar with vaccine guidelines for immunocompromised patients and almost all report barriers in supporting patients regarding vaccines after cancer treatment. Our findings show that further research and interventions are needed to help bridge oncology care and primary care regarding immunizations after treatment.